2011
DOI: 10.1088/0031-9155/56/21/006
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical signatures ofin vitroradiation response in human lung, breast and prostate tumour cells observed with Raman spectroscopy

Abstract: This work applies noninvasive single-cell Raman spectroscopy (RS) and principal component analysis (PCA) to analyze and correlate radiation-induced biochemical changes in a panel of human tumour cell lines that vary by tissue of origin, p53 status and intrinsic radiosensitivity. Six human tumour cell lines, derived from prostate (DU145, PC3 and LNCaP), breast (MDA-MB-231 and MCF7) and lung (H460), were irradiated in vitro with single fractions (15, 30 or 50 Gy) of 6 MV photons. Remaining live cells were harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 84 publications
2
90
1
Order By: Relevance
“…RS has also been used to evaluate radiation response in vitro in mammary epithelial cells, 6 oral cancer cells, 7 prostate tumor cells, 8 and breast and lung tumor cells. 9 The studies cited above involve doses of several Gray, relevant for radiotherapy, however, recent RS applications include investigation of cell response to low radiation doses ( < 1 Gy), relevant for diagnostic radiology or out-of-field radiation in radiotherapy (as well as radiation protection in general). Maguire et al 10 demonstrated that RS is capable of detecting 60 Co radiation response in human lymphocytes for doses as low as 0.05 Gy; DNA damage predicted by changes in Raman spectra were confirmed by comparison with c-H2AX assay results.…”
Section: Introductionmentioning
confidence: 99%
“…RS has also been used to evaluate radiation response in vitro in mammary epithelial cells, 6 oral cancer cells, 7 prostate tumor cells, 8 and breast and lung tumor cells. 9 The studies cited above involve doses of several Gray, relevant for radiotherapy, however, recent RS applications include investigation of cell response to low radiation doses ( < 1 Gy), relevant for diagnostic radiology or out-of-field radiation in radiotherapy (as well as radiation protection in general). Maguire et al 10 demonstrated that RS is capable of detecting 60 Co radiation response in human lymphocytes for doses as low as 0.05 Gy; DNA damage predicted by changes in Raman spectra were confirmed by comparison with c-H2AX assay results.…”
Section: Introductionmentioning
confidence: 99%
“…Human prostate cell lines were found to be radiosensitive whereas breast and lung cells seem to be radio resistant. 77 Radiation induced spectral changes were observed in Raman peaks associated with aromatic amino acids, conformation of protein structures, certain nucleic acid, and lipid functional groups. Lakshmi et al 78 noted a small loss of lipid in trabecular regions with no osteoradionecrosis and a complete loss of lipid in osteoradionecrosis bone in oral cancer patients treated with radiation therapy.…”
Section: C Raman Spectroscopy For Radiation Therapy Response Assesmentioning
confidence: 99%
“…6,7 The radioresistant lung and breast cells showed radiation-induced RS spectral features as glycogen accumulation at low RT doses, whereas the radiosensitive prostate cells showed some membrane phospholipid-related alterations. 8,9 Roman et al analyzed cytoplasmic and nuclear regions of irradiated prostate cancer cells (PC-3) and suggested various DNA damages located in those two regions. 10 Lasalvia et al observed that DNA was damaged in breast cells (MCF10A) irradiated by protons, in particular the O-P-O stretching mode at about 784 cm À1 .…”
Section: Introductionmentioning
confidence: 99%